Management during the war period in the context of social resilience and sustainable development of communities in Zaporizhzhia region - Arabadzhyiev, Dmytro; Sergiienko, Tetiana (Management and Entrepreneurship: Trends of Development, 2025)
The article examines management during wartime as a strategically important tool for ensuring social resilience and sustainable development of communities, using Zaporizhzhia region as a case study. The relevance of the topic is determined by the unprecedented challenges caused by the full-scale invasion, manifested in the destruction of infrastructure, mass population displacement, humanitarian crises, and the transformation of the local self-government system. Under conditions of high uncertainty and constant threats, communities are forced to implement crisis and flexible management models that combine early recovery and anti-crisis measures with a focus on long-term reconstruction and development.The purpose of the study is to substantiate the role of management in shaping the resilience of communities in Zaporizhzhia region, to analyze practices of early recovery, crisis management, and integration of internally displaced persons, as well as to identify prospects for sustainable development of the region in the post-war period. To achieve this goal, a set of methods was applied: analysis of official reports and scholarly sources to determine key management problems; a systemic approach to reveal the interconnection between management decisions, socio-economic processes, and the level of community resilience; comparative analysis methods to assess the effectiveness of management models and identify best practices.The study concludes that effective governance in wartime is based on flexibility, recognition and consideration of cascading risks under strategic uncertainty, the ability to adapt quickly to changes, and maintaining a balance between urgent population needs and long-term recovery prospects. The key factors of community resilience are identified as: adaptability, social cohesion, digitalization of management processes, involvement of civil society, support for internally displaced persons, coordination with international organizations, and the development of post-war recovery strategies. The practical significance of the results lies in the possibility of applying the experience of Zaporizhzhia region by state authorities, local governments, and international partners in developing recovery policies and implementing sustainable development models for regions in crisis and post-crisis conditions.JEL Classification: H12, H70, O18, Q01, R58